(untitled) (International Journal of Nursing Education, 2021)
Background: Osteoporosis is a silent killer disease that is highly prevalent among females. Even though the symptoms of osteoporosis can be identified in later stages of life, it can be prevented with a healthy lifestyle adaptation at an early stage of life. Objectives: The present study aims to assess the knowledge level of osteoporosis among young adult females and examine the association between knowledge level and selected socio-demographic variables. Methodology: A quantitative descriptive cross-sectional study design was used. A non-probability purposive sampling technique was used to select 153 samples. The data were collected for 6 weeks using a semistructured interview schedule. Osteoporosis Knowledge assessment tool (OKAT) was used to collect the data. Descriptive statistics (frequency, percentage, mean, standard deviation) was used for quantitative data analysis and inferential statistics (chi-square) were used to find out the association between knowledge level and selected socio-demographic characteristics of the respondents. Results: The study concluded that 51 percent of the young adult women had an average level of knowledge and 49 percent had a poor level of knowledge regarding osteoporosis. However, none of them had a good level of knowledge regarding osteoporosis. A significant association was found between the knowledge level and educational status of the respondents (p=0.002).